2022
DOI: 10.1088/2057-1976/ac6196
|View full text |Cite
|
Sign up to set email alerts
|

Development of the PhysioVessel: a customizable platform for simulating physiological fluid resuscitation

Abstract: Uncontrolled hemorrhage is a leading cause of death in trauma situations. Developing solutions to automate hemorrhagic shock resuscitation may improve the outcomes for trauma patients. However, testing and development of automated solutions to address critical care interventions, oftentimes require extensive large animal studies for even initial troubleshooting. The use of accurate laboratory or in-silico models may provide a way to reduce the need for large animal datasets. Here, a tabletop model, for use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Hemorrhage data was compiled from a previous swine study [ 16 ] and analyzed using MATLAB (MathWorks, Natick, MA, USA) to assess the relationship between bolus infusion volume of whole blood (WB) and mean arterial pressure (MAP). Animal subjects underwent a controlled hemorrhage of 24 mL/kg followed by a spleen injury prior to the bolus infusion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hemorrhage data was compiled from a previous swine study [ 16 ] and analyzed using MATLAB (MathWorks, Natick, MA, USA) to assess the relationship between bolus infusion volume of whole blood (WB) and mean arterial pressure (MAP). Animal subjects underwent a controlled hemorrhage of 24 mL/kg followed by a spleen injury prior to the bolus infusion.…”
Section: Methodsmentioning
confidence: 99%
“…The loop included two PhysioVessels that acted as the venous capacitance for the system: one for mimicking whole blood (PV WB ) and the second for mimicking crystalloid (PV Crys ). We have previously shown that these PhysioVessels were constructed based on pressure–volume relationship functions derived from experimental swine hemorrhagic shock resuscitation data, such that the geometry of the PhysioVessel causes hydrostatic pressure to mimic volume responsiveness during fluid resuscitation with different fluids [ 16 ]. This empiric approach was meant to circumvent the need for a complex physiological model but it has its limitations due to the data it is based on, meaning its use is limited to healthy swine subjects with their volume status in the range between profound shock (loss of over 35% of estimated blood volume) and damage-control resuscitation goals, with the resuscitation performed using either whole blood or crystalloids.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example for such a testing platform is reported by Bighamian et al [ 18 ]. This method allows for high-throughput tests of the controller at minimal cost and time, using only a computer on existing datasets but cannot test the hardware components; Hardware-in-loop (HIL) testing —A testing method that incorporates hardware components in a physical, manufactured system that simulates a variety of patient scenarios, while measuring the closed-loop controlled system’s performance [ 19 ]. These systems can sometimes be merged with an in silico simulation platform [ 20 ]; In vivo studies (animals) —Testing the entire system’s performance in a real, whole-body physiological system, with subject variability, allows for the additional validation for the system’s performance and enabling measurements of the additional relevant data, such as biochemical markers.…”
Section: Introductionmentioning
confidence: 99%